DEVELOPMENT OF SCIENCE PROCESS SKILLS (SPS) – ORIENTED LEARNING MATERIALS ON GLOBAL WARMING TO STIMULATE STUDENTS’ LITERACY - Syuhada Amelia; Monica Prima Sari (Department of Science Education, 2021)
In the ever-changing world today, improving students’ literacy skills has become urgently needed. However, in reality most students still lack of interest in literacy. The purpose of this research is to produce a valid and practical Science Process Skills (SPS) – oriented learning material on Global Warming that is suitable for VII grade in secondary school. This research and development (R&D) study used ADDIE model, which consists of five steps namely: Analysis, Design, Develop, Implementation, and Evaluation. A set of questionnaires to test validity was distributed to three validators and another set of questionnaires to test practicality was distributed to seventh-grade students of SMP Negeri 24 Padang in the academic year of 2019/2020. The result shows that the developed learning material is valid and highly practical to be used in secondary school science lesson. Moreover, this learning materials helped stimulate students’ scientific literacy skills in understanding the lessons.